Quality of life, self-esteem, and happiness in women from mid-high and low socioeconomic status during climacteric in the City of Lima - Olaechea Ramírez, María Sonia (2012)
The objective of this research is to identify the relationship between the following variables: quality of life, selfesteemand Happiness, considering factors such as age, marital status, level of education and working status. Thesample is composed by 221 women of mid-high and low socioeconomic status in the city of Lima, Peru.The results show evidence that these changes do not significantly affect the behavior of the women in this study;however, the symptoms have different effects on each phase of the climacteric period. These women show high levelsof self-esteem and moderate level of quality of life and happiness. The results also show significant correlationamong the three variables in this study.